The determinants of bank interest rate spreads in Malaysia / Norashikin Malik - Malik, Norashikin (2008)
This paper was study the determinant of commercial bank interest rate spread in Malaysia during the period of 1997-2006 by using all commercial bank as a sample. This paper empirically analyzes all macroeconomic factors that would affect the behavior of such rates. The study has used multiple regression method to see the relationships between dependent and independent variables. Bank interest rate spread was used as the dependent variable and inflation rate, interest rate volatility, economic activity in term of Gross Domestic product (GDP), which is all of this are also known as external factors or macroeconomic factors that were used as independent variables. The role played by the inflation rate, interest rate volatility and economic activities (gross domestic product) which is also known as macroeconomics factors were highlighted. The result suggests that all macroeconomics factors were the most relevant factors to explain the behavior of bank interest rate spread in Malaysia